Design of Integral Sliding Mode Controller for Servo DC Motor - Midhat, Bashar Fateh; Humaidi, Amjad Jaleel; Raheem, Firas A. (Al-Nahrain Journal for Engineering Sciences, 2017)
DC servo motor is simple in construction and control and has many applications. However, the uncertainties due to its parameters changes such as load torque and friction are an evitable. Therefore, a robust controller has to be employed for keeping specified requirements irrespective to parameter variations. In the present work, two sliding mode controllers have been suggested to control the speed of DC motor under motor load changes; classical and integral sliding mode controllers. The integral slide mode control could show better tracking characteristics than its counterpart and also could compensate the change in system parameters.